PENGARUH INOVASI PRODUK, AKSES PERMODALAN, DAN AMBIDEXTERITAS KONTEKSTUAL TERHADAP KINERJA UKM - Sinaga, Gilbert Johan Martin; Desmiyawati; Susilatri (Badung Bali: Politeknik Negeri Bali, 2025)
This study aims to examine the effect of product innovation, access to capital, and contextual ambidexterity on the performance of SMEs in Pekanbaru City. This study uses a quantitative causality approach to answer the formulation of problems and research hypotheses. The population in this study were all SMEs in Pekanbaru City which amounted to 25,074 units. The sampling technique chosen was purposive sampling. The number of samples obtained was 394 SMEs using the Slovin formula. The type of data used is primary data and data collection techniques using questionnaires. Data analysis using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.0 software. The novelty in this study is that contextual ambidexterity variables are still rarely studied in SMEs in Indonesia and several previous studies also show a research gap. The results obtained are product innovation, access to capital, and contextual ambidexterity have a positive and significant effect on SME performance.